Cytotoxic Effects of Alcoholic Extract of Dorema Glabrum Seed on Cancerous Cells Viability - Maryam Bannazadeh Amirkhiz; Nadereh Rashtchizadeh; Hosein Nazemieh; Jalal Abdolalizadeh; Leila Mohammadnejad; Behzad Baradaran (Tabriz University of Medical Sciences, 2013)
Purpose: In the present study cytotoxic effects of the alcoholic extract of Dorema Glabrum seed on viability of WEHI-164 cells, mouse Fibrosarcoma cell line and L929 normal cells were compared with the cytotoxic effects of Taxol (anticancer and apoptosis inducer drug). Methods: To find out the plant extract cytotoxic effects, MTT test and DNA fragmentation assay, the biochemical hallmark of apoptosis were performed on cultured and treated cells. Results: According to the findings the alcoholic extract of Dorema Glabrum seed can alter cells morphology and because of chromatin condensation and other changes they shrink and take a spherical shape, and lose their attachment too. So the plant extract inhibits cell growth albeit in a time and dose dependent manner and results in degradation of chromosomal DNA. Conclusion: Our data well established the anti-proliferative effect of methanolic extract of Dorema Glabrum seed and clearly showed that the plant extract can induce apoptosis and not necrosis in vitro, but the mechanism of its activities remained unknown. These results demonstrated that Dorema Glabrum seed might be a novel and attractive therapeutic candidate for tumor treatment in clinical practices.